A Synthesis of Novel Perinaphthenones from Acetylenic Esters and Acenaphthoquinone–Malononitrile Adduct in the Presence of Triphenylphosphine - Yavari, Issa; Khajeh-Khezri, Aliyeh; Halvagar, Mohammad Reza (Synlett, 2018)
A facile protocol involving Tebby zwitterions (PPh3-acetylenic esters) and the Knoevenagel condensation product of acenaphthylene-1,2-dione with malononitrile or ethyl cyanoacetate for the selective synthesis of a new series of perinaphthenone derivatives is described. Triphenylphosphine plays a catalytic role in these transformations. The structure of a typical product was confirmed by X-ray crystallography. The merits of this method include high yields of products, good atom economy, and a metal-free catalyst.
Keywords: perinaphthenones; acenaphthylenedione; alkynoate esters; triphenylphosphine; malononitrile